Multivariate Base Rates of Low Scores on Tests of Learning and Memory Among Latino Adult Populations. (27th May 2019) - Rivera, Diego; Olabarrieta-Landa, Laiene; Brooks, Brian L.; Ertl, Melissa M.; Benito-Sánchez, Itziar; Quijano, Maria Cristina; Rodriguez-Irizarry, Walter; Aguayo Arelis, Adriana; Rodríguez-Agudelo, Yaneth; Arango-Lasprilla, Juan Carlos
Abstract: Objective: To determine the prevalence of low scores for two neuropsychological tests with five total scores that evaluate learning and memory functions. Method: N = 5402 healthy adults from 11 countries in Latin America and the commonwealth of Puerto Rico were administered the Rey–Osterrieth Complex Figure (ROCF) and the Hopkins Verbal Learning Test (HVLT-R). Two-thirds of the participants were women, and the average age was 53.5 ± 20.0 years. Z -scores were calculated for ROCF Copy and Memory scores and HVLT-R Total Recall, Delayed Recall, and Recognition scores, adjusting for age, age 2, sex, education, and interaction variables if significant for the given country. Each Z -score was converted to a percentile for each of the five subtest scores. Each participant was categorized based on his/her number of low scoring tests in specific percentile cutoff groups (25 th, 16 th, 10 th, 5 th, and 2 nd ). Results: Between 57.3% (El Salvador) and 64.6% (Bolivia) of the sample scored below the 25 th percentile on at least one of the five scores. Between 27.1% (El Salvador) and 33.9% (Puerto Rico) scored below the 10 th percentile on at least one of the five subtests. Between 5.9% (Chile, El Salvador, Peru) and 10.3% (Argentina) scored below the 2 nd percentile on at least one of the five scores. Conclusions: Results are consistent with other studies that found that low scores are common when multiple neuropsychological outcomes are evaluated in healthy individuals. Clinicians should consider the higher probability of low scores when evaluating learning and memory using various sets of scores to reduce false-positive diagnoses of cognitive deficits.